Effects of clofibrate, silybin, safflower oil and lamindran on liver peroxisome proliferation and enzyme activities in rats - WU Shu-guang; SHEN You-an; ZHENG Zun; LONG Kun (Acta Pharmacologica Sinica, 2016)
Clofibrate (500 mg/kg/d ig to rats for 4 weeks, caused hepatomegaly, hepatic peroxisome proliferation and increment of catalase and carnitine acetyltransferase (CAT) activities, while silybin (600 mg/kg/d), safflower oil (5 ml/kg/d) and lamindran (100 mg/kg/d) did not. From these observation, it is suggested that the changes in liver caused by hypolipidemic drugs might be not related to the hypolipidemic action of drugs.